(untitled) (Forseti. Law Review, 2025)
The incorporation of artificial intelligence into the judicial system raises tensions with constitutional principles such as due process, the reasoning of decisions, and the guarantee of a natural judge. From an ethical-legal perspective, this article examines Law No. 31814, highlighting its normative insufficiencies in addressing algorithmic risks, and proposes criteria for a substantively just regulation.